The emotional journey of being and becoming bilingual. Issue 2 (7th February 2020) - Moate, Josephine; Ruohotie-Lyhty, Maria
ABSTRACT: This article examines the foreign language learning biographies of six Finnish English speakers who reflect on their journey towards a bilingual identity. In this article language learning is examined as a process that is intrinsically emotional as emotion connects individuals with the world as well as being a movement within oneself. The data analysis is based on dialogical and narrative approaches. Through the analysis two key story types were named: Bilingualism as striving and Bilingualism as a gift . In the striving stories English was held up as an ideal, as a way of engaging with the wider world but moreover as a way of finding a better 'me'. In the gift stories, English was experienced as a gateway to something other, whether a new community, sport, or music. The emotional intonation of these two story types varied considerably highlighting the importance of emotion within language education.